Reform-törekvések Kovács István munkásságában az alapvető jogok alkotmányi szabályozása kérdésében - Kiss Barnabás; Kovács István (2021)
During his outstanding professional career of forty years, István Kovács played a decisive role – as a professor at law and as well as the head of the Institute of Law and Political Science (Hungarian Academy of Sciences) – in the teaching and researching of Hungarian constitutional law. In the field of constitutional development, he always paid great attention to the regulation of citizen's /constitutional/ rights and then human rights. The study aims to show, how Kovács came up with proposals that were beyond his age in the course of Constitutional attempts, despite the ideological and political constraints of the socialist era. The results of his work were well documented in the draft constitution of 1962 and the implemented constitutional revision in 1972. In 1988, he described an idea of a constitution that had already proved suitable for the preparation and implementation of the regime change in Hungary. The article argues that Kovács' proposals, despite the constraints of the given period, have always been progressive, and some of them can still be considered relevant in the regulation of human and constitutional rights.
Keywords: Társadalomtudományok; Jogtudomány